The Impact of Price, Brand Image, and Service Quality on Consumer Purchase Decisions - Vivin Wulandari Vivin Wulandari; dewi fadila; sari lestari zainal ridho (Department of Business Administration Politeknik Negeri Sriwijaya, 2022)
This study aims to comprehensively analyze the influence of price, brand image, and service quality on the purchase decision of vehicle insurance products at PT Asuransi Etiqa Internasional Indonesia, Palembang Branch. Vehicle insurance is a crucial form of financial protection favored by consumers to mitigate the risks of damage, loss, or accidents involving motor vehicles. In the face of increasing competition within the insurance industry, companies are required to understand the factors influencing consumer behavior in order to develop effective marketing strategies. This research adopts a quantitative approach through a survey method, collecting data from 85 respondents who are active policyholders. The data were analyzed using multiple linear regression with SPSS version 25. The results reveal that all three independent variables-price, brand image, and service quality-have a statistically significant influence on purchase decisions, both individually and collectively. Among these factors, service quality emerges as the most dominant variable affecting consumer choices in purchasing vehicle insurance products. These findings indicate that consumers consider not only price and brand reputation but also place high importance on the service experience they receive, from the initial engagement to post-purchase interactions. Therefore, in order to foster customer loyalty and expand market share, insurance providers are advised to continuously enhance service quality, maintain competitive and reasonable pricing strategies, and consistently strengthen brand image through effective communication and positive customer relations.